Amyand's hernia: 11 years of experience - Cigsar, Emine Burcu; Karadag, Cetin Ali; Dokucu, Ali Ihsan (W B Saunders Co-Elsevier Inc, 2016)
Purpose: Presence of the vermiform appendix in an inguinal hernia sac is known as Amyand's hernia. This may present as a tender inguinal swelling and is often misdiagnosed as irreducible or strangulated hernia. Methods: Between January 2003 and December 2013 we treated 4498 patients with inguinal hernias and performed 3267 appendectomies. Among these; 46 had an Amyand's hernia. Age, sex, presenting symptoms, treatment modality, histopathological findings, duration of hospitalization, and post-surgical outcomes were analyzed retrospectively. Results: All patients were boys. The mean age was 16.7 months (15 days-8 years). 37 (80.4%) right, 2 (4.3%) left and 7 (15.2%) bilateral hernioplasties were performed. Nine patients underwent emergency surgery with an initial diagnosis of incarcerated hernia; Amyand's hernia was an incidental finding in the remaining 37 patients. Operative findings included 33 normal appendices, 9 inflamed appendices, one perforated appendix, and three appendices adherent to the hernia sac. Eighteen patients had appendectomy during hernia repair, and the other 33 had hernia repair without appendectomy. None of the patients developed recurrent hernia or appendicitis within the follow-up period. Conclusion: In Amyand's hernia the appendix should be examined carefully. A classification of Amyand's hernia according to the presenting symptoms and inflammatory status of the appendix may help to determine whether or not to proceed with appendectomy. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Amyand's hernia; inguinal hernia; Appendectomy; Prophylactic appendectomy; Classification